(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
The term ‘Brata’ finds its etymological roots in the Sanskrit verb ‘Bri’ (to grow, to strengthen) with the addition of the suffix ‘Ata’, collectively signifying a disciplined ritual vow. The core meaning of Brata is a sacred vow or a set of observances. It is a ritual performance driven by a specific desire, undertaken through strict discipline to achieve spiritual or worldly fulfillment. The observance of a Brata is believed to eradicate sin and accumulate virtue (Punya). Scholarly typologies generally classify Bratas into two primary categories: the Shastriya or Puranic (scriptural) Bratas and the Ashastriya or Lokakriti (non-scriptural or folk) Bratas. The folk Bratas are further subdivided into three types: those observed exclusively by women, those by men, and those observed communally by both. These Bri ceremonies served as an important cultural outlet for women, enabling emotional expression and social interaction. Through these events, women engaged in music, poetry, dance, drama, and storytelling, satisfying their artistic and social aspirations. Historically, Bri performances took place predominantly within Brahmin communities. Among these, the performances put on by unmarried girls- referred to as the ‘Maiden Bri’ or ‘Kumari Bri’- are particularly prominent. Among Bengal’s well-known Kumari Bri groups are Kulkulti Bri, Dashputtli Bri, Yam Pukur Bri, Harir Charan Bri and Ashwatthapata Bri etc. These groups are characterized by their vocal and dance performances, often involving multiple maiden troupes who gather to present varied forms of art. Their performances include intricate designs known as alpana, rhythmic chanting, and compelling storytelling. The lyrics are rich with literary devices such as metaphors and similes, evoking deep emotions and vivid imagery. The Kumari Bri performances- marked by their melodiousness and enchanting aesthetics- reflect the high aesthetic sensibility and cultural refinement of the maidens involved. These traditions continue to draw admirers and enthusiasts, with some performers gaining regional recognition. The Bri art forms are deeply interwoven with Bengali cultural and spiritual beliefs, and the stories told through them encapsulate collective values and histories. Choreography and ritualistic movements accompany these performances, with maidens primarily undertaking the dances, though occasionally women of other communities also participate. While traditional social norms sometimes place restrictions on female public performances, these Bri festivities historically contributed to promoting women’s social presence and rights. Despite the transformations brought by modern urbanization, the Kumari Bri traditions remain a vital cultural heritage of Bengal. Preserving and celebrating these folk art forms continue to be essential for maintaining the richness and diversity of Bengali cultural identity.